The net impact of telework on restaurant revenues in Canada - Tahsin Mehdi; René Morissette (Economic and Social Reports)
Using monthly provincial data that cover the period from March 2020 to July 2022, this study quantifies the association between work from home and revenues in the food services and drinking places subsector. Controlling for changes in COVID-19 restrictions and Canadians’ health concerns, the study estimates that an increase of 1 percentage point in the monthly incidence of work from home was associated with a 0.55 percentage point reduction in the monthly growth rate of receipts in food services and drinking places in a given province during that period. Simple calculations based on these estimates suggest that the increase in work from home observed from February 2020 to April 2020 accounted for about one-third of the drop in revenues observed in this subsector between these two months.